2004
DOI: 10.1021/ol036290g
|View full text |Cite
|
Sign up to set email alerts
|

A General and Mild Ullmann-Type Synthesis of Diaryl Ethers

Abstract: [reaction: see text] An efficient method for the synthesis of diaryl ethers under particularly mild conditions is described. Inexpensive ligands were found to greatly accelerate the Ullmann-type coupling of aryl bromides or iodides with phenols. A series of diaryl ethers were obtained with excellent yields in acetonitrile in the presence of Cs(2)CO(3) and catalytic copper(I) oxide. The reaction tolerates substrates with unfavorable substitution patterns, such as sterically hindered coupling partners or electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(113 citation statements)
references
References 31 publications
2
109
0
2
Order By: Relevance
“…Cu and Co particle size can play an important role in the catalytic activity as reported by Gedanken [41]. As observed previously in our group [22] the precipitation of LDH onto graphene oxide leads to a smaller particle size if compared with the unsupported LDH due to a nucleation effect.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Cu and Co particle size can play an important role in the catalytic activity as reported by Gedanken [41]. As observed previously in our group [22] the precipitation of LDH onto graphene oxide leads to a smaller particle size if compared with the unsupported LDH due to a nucleation effect.…”
Section: Resultssupporting
confidence: 74%
“…In principle, this reaction requires harsh reaction conditions, such as large excess of phenols, high temperatures (>200 °C) and at least stoichiometric amounts of copper, which result in the production of undesirable chemical waste [40]. Besides, most of the Cu based catalysts need an extra base and/or require long reaction times [41,42]. As an alternative palladium, gold and nickel based catalysts have been introduced [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Cheap K 2 CO 3 showed a satisfactory yield and was chosen for the O-arylation reaction (entry 14). The isolated yield increased sharply with the increase of reaction temperature (entries [14][15][16]. The copper concentration in the reaction mixture was another important factor to investigate.…”
Section: Catalytic Activity Studymentioning
confidence: 99%
“…The results clearly revealed that an electron-withdrawing group in the aryl bromides favored the coupling reactions (Table 4, entries 24-29 vs 1-4, 10), however an electron-releasing group in the aryl bromides went against the coupling reactions. For example 4-methylbromobenzene could be coupled with phenol to give the products in 59-85% yields (Table 4, entries [11][12][13][14][15][16][17][18], yet aryl bromides with electron-withdrawing substituents, e.g. 2-acetylphenyl bromide, afforded the corresponding products in 86-95% yields (Table 4, entries 24-25, 27-28) with the exception of 4-cyanophenol, which led to a low yield (56%) for the coupling reaction (Table 4, entry 29).…”
Section: Notesmentioning
confidence: 99%